Comanagement with rheumatology and prescription biologics filled during pregnancy in women with rheumatic diseases: a retrospective analysis of US administrative claims data - Jonathan Kay; Kate L Lapane; Divya Shridharmurthy; Jonggyu Baek; Anthony Nunes; Shao-Hsien Liu (BMJ Open)
Objectives To evaluate comanagement with rheumatology and biological prescriptions filled during pregnancy among women with axial spondyloarthritis (axSpA), rheumatoid arthritis (RA) or psoriatic arthritis (PsA) and to examine factors associated with receiving comanagement with rheumatology during pregnancy.Design A retrospective analysis of US claims data.Setting Commercially insured enrollees using data from the 2013–2018 IBM MarketScan Commercial Claims and Encounters Database.Participants We identified 4131 pregnant women aged ≤55 years from the 2013–2018 IBM MarketScan Commercial Claims and Encounters Database with an International Classification of Disease, 9th Revision/10th Revision codes for RA, axSpA or PsA, with continuous enrolment at ≥3 months before the date of the last menstrual period (LMP) (index date) and throughout pregnancy.Primary outcomes Filled biologics (prescriptions and infusions) claims were categorised by 90 days before the LMP and trimester, as were primary care, obstetrician and rheumatological claims.Results The prevalence of axSpA, RA and PsA was 0.7%, 0.2% and 0.04% among reproductive age women. The average maternal age was 32.7 years (SD 5.7). During pregnancy, 9.1% of those with axSpA (n=2,410) and 56.4% of those with RA/PsA (n=1,721) had a rheumatological claim. Biologics claims were less common among those with axSpA (90 days before LMP: 1.6%, during pregnancy: 1.1%) than those with RA/PsA (90 days before LMP: 11.9%, during pregnancy: 6.9%). Medications during pregnancy included corticosteroids (axSpA: 0.3%, RA/PsA: 2.2%), non-biological disease-modifying antirheumatic drugs (axSpA: 0.2%, RA/PsA: 1.7%), non-steroidal anti-inflammatory drugs (axSpA: 0.2%, RA/PsA: 1.3%) and opioids (axSpA: 0.2%, RA/PsA: 0.6%). Established rheumatological care and biologics claims during the 90 days before LMP showed good prediction accuracy for receiving comanagement with rheumatology during pregnancy (axSpA: area under the receiver operator curve (AUC) 0.73, RA/PsA: AUC 0.70).Conclusion Comanagement with rheumatology during pregnancy occurs infrequently, especially for women with axSpA. Biologics claims during pregnancy may not align with published guidelines. Future research is warranted to improve comanagement with rheumatology during pregnancy.